2022
DOI: 10.1093/ofid/ofac492.1000
|View full text |Cite
|
Sign up to set email alerts
|

1163. Age, Poverty and Inequity are Key Determinants of Dengue Severity in Colombia

Abstract: Background Age has been a major risk factor for death and complication due to dengue infection (DENV). Although antibody-dependent enhancement (ADE) has been proposed as an explanation, other variables could shape disease outcomes. We aimed to analyze the role of age as a risk factor for disease severity across departments (first administrative level), and epidemic years in Colombia considering poverty and inequity indexes. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A systemic literature review exploring 12 studies across Southeast Asia and Latin America found mixed results between studies on associations between different poverty indicators and dengue burden [109]. Other studies suggest poverty may lead to increased dengue severity, though this may also be due to other covariates specific to the geographic region [110][111][112]. A recent systematic literature review found that lower income and rural settings were among several barriers to seeking healthcare for dengue [113].…”
Section: Discussionmentioning
confidence: 99%
“…A systemic literature review exploring 12 studies across Southeast Asia and Latin America found mixed results between studies on associations between different poverty indicators and dengue burden [109]. Other studies suggest poverty may lead to increased dengue severity, though this may also be due to other covariates specific to the geographic region [110][111][112]. A recent systematic literature review found that lower income and rural settings were among several barriers to seeking healthcare for dengue [113].…”
Section: Discussionmentioning
confidence: 99%